TRANSLATION STRATEGIES AND STYLISTIC BALANCE IN LITERARY PROSE - Isabelle Laurent, Marco Rossi (International Journal of Literature and Language Studies, 2024)
This article examines translation strategies and stylistic balance in literary prose through a focused qualitative lens. Drawing on multiple English renderings of short prose passages originally written in European languages, the study uses comparative textual analysis focusing on lexical density, register, rhythm, and cultural transfer to identify how meaning, voice, and interpretation are shaped in literary and linguistic practice. The analysis shows that literal transfer preserved semantic detail but often flattened rhythm and imagery, adaptive translation better maintained literary voice when cultural references required mediation, while the third finding highlights how textual structure or interactional pattern helps sustain the broader effect. The paper argues that close attention to language form remains essential for understanding how literary texts and communicative events produce emotion, identity, and social meaning. It also demonstrates that careful reading can connect stylistic detail with wider cultural and pedagogical questions.